ANALISIS BEBAN KERJA PETUGAS TERMINAL INSPECTION SERVICE (TIS) DI BANDAR UDARA DEPATI AMIR PANGKAL PINANG - Anjeli Pratiwi; Annike Resty Putrie (MANAJEMEN, 2023)
The purpose of this study was to determine the constraints and work overload of terminal inspection service (TIS) unit officers working at Depati Amir Pangkal Pinang Airport. Terminal inspection service (TIS) unit officers play an important role in providing and prioritizing effective and stable services to airport service users, especially in monitoring, checking, maintaining, and handling facilities in the airport terminal area. The research was conducted at Depati Amir Pangkal Pinang Airport, this type of research used qualitative methods. Source of data in this study using secondary data and primary data. And for data collection techniques in this study using observation, interviews, and documentation. The results of this study can be concluded that the terminal inspection service (TIS) unit officers at Depati Amir Airport have carried out work professionally, but there are constraints and work overload responsibilities by terminal inspection service (TIS) officers such as doing work that is not the duty of the terminal inspection service (TIS) unit, staff shortages and unstable work times that have an impact on employee performance.